2019
DOI: 10.1002/jimd.12035
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics and outcomes of patients with formiminoglutamic aciduria detected through newborn screening

Abstract: Summary Background Glutamate formiminotransferase deficiency (FTCD deficiency) or formiminoglutamic aciduria is the second most common of the known inherited disorders of folate metabolism. Initial case reports suggested that patients may have severe intellectual disability and megaloblastic anemia. However, these cases were obtained from screening cohorts of patients with developmental delay. Subsequently, patients with milder clinical phenotypes have been reported. The full phenotypic spectrum of this disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Among all the FTCD deficiency patients, the cases displaying symptoms are limited. Recently, a tandem mass spectrometry-based newborn screen suggested that the majority of individuals with FTCD deficiency were asymptomatic [44]. That is consistent with the ftcd mutant zebrafish under normal feedings.…”
Section: Discussionmentioning
confidence: 53%
“…Among all the FTCD deficiency patients, the cases displaying symptoms are limited. Recently, a tandem mass spectrometry-based newborn screen suggested that the majority of individuals with FTCD deficiency were asymptomatic [44]. That is consistent with the ftcd mutant zebrafish under normal feedings.…”
Section: Discussionmentioning
confidence: 53%
“…Continuing to expand NBS, SMA was added to the screening panel on 30 August 2023 by the National Board of Health and Welfare policy development [ 1038 ]. Regarding other conditions, a study developed G6PD incidence data and found that NBS was probably not warranted [ 1039 ], two studies looked at the possibility of analyzing DBSs for phosphatidylethanol, an alcohol biomarker [ 1038 , 1040 ], and another study looked at the characteristics and outcomes of patients with formiminoglutamicc aciduria detected through NBS [ 1041 ]. In the long term, NBS may be significantly impacted by a new project, Screen4Care, which draws on a collaboration of 21 academic partners, 9 industrial project partners, and 4 small- and medium-sized enterprises to initiate a multi-pronged strategy to shorten the time to diagnosis and treatment for patients with rare diseases through genetics and artificial intelligence [ 1042 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, increasing concentrations of methylsuccinic acid (MSA) concentration serves as a special biochemical marker for EE (8), and elevations in OX-2acetoacetic acid, isovalanyl glycine-2,2-hydroxyisobutyric acid-2, and adipic acid to extremely high levels are observed in GA2 (9). In some cases of FIGLU, formiminoglutamate is observed in biological fluids after histidine loading (10). Therefore, a novel second-tier screening method involving the use of UPLC-MS/MS can detect the secondary targets ethylmalonic acid (EMA) and isobutyryl-glycine (IBG), which are part of the differential diagnosis or profile review of screening for primary targets (11,12).…”
Section: Introductionmentioning
confidence: 99%